Rhetoric, public discussion and the dispute over rationality - Škerlep, Andrej (Javnost-The Public, 2004)
The article confronts Plato’s early critical rejection of rhetoric and Aristotle’s response to that critique with a positive definition of rhetoric in his philosophical system. In the first part, Plato’s critique of rhetoric in a dialogue with Gorgias is presented, which he builds on the opposition between the persuasiveness of rhetoric and true knowledge. He develops the argument that rhetoric manipulates the audience and is, therefore, unethical. The second part of the article focuses on Aristotle’s understanding of rhetoric in the context of his system of three categories of human knowledge and in relation to three methods of reasoning. The article sides with Aristotle’s claim that because of the contingent nature of public issues and popular audience, rhetorical argumentation cannot fulfil those lofty criteria proposed by Plato. But, according to Aristotle, this does not degrade the status of rhetoric.